Contribution to Hydrogeological Knowledge of the Turonian-Coniacian Aquifer Exploited in the Coastal Sedimentary Basin of Benin-Togo - Cherguie Mellone Extraila Glessougbe; Alassane Abdoukarim; Kodjo Apelete Raoul Kpegli; Gnandi Kissao; Bio Guidah Chabi; Alassane Zakari Aoulatou; Daouda Mama; Moussa Boukari (European Scientific Journal, ESJ, 2026)
Our article contributes to improving hydrogeological knowledge of the Turonian-Coniacian aquifer in the Benin-Togo coastal sedimentary basin by determining the geometry, structure, and piezometry of this aquifer in the northern part of the Benin-Togo coastal sedimentary basin. The structure of the Turonian-Coniacian aquifer was determined through geological and hydrogeological correlation of existing logs from thirty-three boreholes on the northern plateaus of the Benin-Togo coastal sedimentary basin. Three cross-sections were created (in Benin and Togo) using the traditional method, combining topographic maps, graph paper, and QGIS 2.18.15. Piezometry was then carried out in three stages: determination of the altitudes of the measurement points (56 wells), calculation of the piezometric levels, and interpolation of the calculated piezometric levels. The piezometric map was produced successively using Excel, Surfer 11, and QGIS 2.18.15.A total of five layers were identified following the hydrogeological sections carried out. These are the lateritic layer (2 to 15 m from north to south); the sandy layer (extending up to 25 m); the very thick clay layer (60 m in the south, 200 m in the Lama depression, and almost absent in the north); the clayey-sandy layer (varying from 4 to 25 m in some areas); and the limestone layer (embedded in the clay layer, reaching up to 20 m in thickness). The Coniacian-Turonian aquifer outcrops north of the northern plateaus of the Benin-Togo coastal sedimentary basin. As the flow direction is mainly north-south, it can be deduced that the aquifer is recharged by rainwater infiltration in its outcrop areas.Although the resource is natural, as is its renewal, it is important that the nations that exploit it, including Benin and Togo, reach a consensus on its efficient use in order to avoid any conflict in the future.